Analysis of the BLUD puskesmas UPTD strategy to achieve organizational effectiveness using the SPACE Matrix Approach - Heruddin, Heruddin; Suryaningsih, Ika Barokah; Dewanto, Iwan (Goodwood Publishing, 2025)
Purpose: This study aimed to analyze the strategy of the UPTD Health Center with BLUD status in Jember Regency using the SPACE matrix approach. Method: This research was a quantitative descriptive study. Data processing and analysis were performed by quantitative analysis using the SPACE matrix, and data collection was conducted in a cross-sectional manner. The sample size of four health centers was selected using the purposive sampling technique. The primary data collection technique using questionnaire instruments was then validated using focus group discussions (FGD) and partly using secondary data from the Health Center. Results: The results of the SPACE matrix analysis show that Health Centers with weak internal strength are in the competitive quadrant, while Health Centers with strong internal strength are in the aggressive quadrant. The two categories of Health Centers are measured in the effectiveness of their organizations based on aspects of financial performance with BLUD maturity indicators showing liquidity results at level 5 (optimizing), efficiency at level 3 (Defined), effectiveness at levels 4 and 5 (Predictable and Optimizing), and maturity levels at level 5 (optimizing) and in terms of service performance, namely, the Community Satisfaction Index with good results for health centers that have weak internal strength and are very good at health centers with strong internal strength. Conclusions: Health centers with strong internal capacity are in the aggressive quadrant and can pursue proactive strategies, whereas weaker ones fall in the competitive quadrant and require cost control. Overall, BLUD status enhances financial and service performance. Limitations: The study was limited to four centers in one region and used cross-sectional data, which may not reflect broader or long-term trends. Contribution: This study applies the SPACE Matrix to guide strategic planning for BLUD health centers based on their internal and external conditions.